Inner Plexiform Layer Substrata Are Discernible with Commercial OCT and Affected by Aging - Victor S.M.C. Correa, MD; Maria Emfietzoglou, MD; Gustavo Sakuno, MD, PhD; Rosanne Naafs, MSc; Joan W. Miller, MD; Alexander Charonis, MD; Demetrios G. Vavvas, MD, PhD (Ophthalmology Science, 2025)
Purpose: This study aims to evaluate the inner plexiform layer (IPL) microstructure and its changes with aging using commercial spectral-domain OCT macular scans of healthy individuals with a semiautomated segmentation program. Design: Cross-sectional study conducted at the Athens Vision Eye Institute from January to July 2024. Participants: The study included 92 healthy participants. Methods: OCT images were captured with the Optovue Avanti SD-OCT and processed using ImageJ to measure thickness and analyze the hyperreflective and hyporeflective bands within the IPL. Information about signal intensity, microstructure, and contrast between these sublayers was obtained. Statistical analyses, including Spearman correlation and linear regression, assessed relationships between age and IPL extracted features. Intraeye and intereye repeatability were evaluated using paired samples t tests combined with bootstrap analyses. Main Outcome Measures: The primary outcomes measured were signal intensity of the IPL, contrast between its hyperreflective and hyporeflective bands, and the percentage of IPL with identifiable sublayers. The secondary outcomes included inner retinal thickness measurements, including the IPL, nerve fiber layer (NFL), and ganglion cell complex (GCC). Results: The IPL exhibited a multilayered structure with 5 sublayers, 3 hyperreflective and 2 hyporeflective, arranged in an alternating pattern. Aging was associated with higher signal intensity from hyporeflective bands and minimal changes in hyperreflective bands, resulting in an overall reduced contrast between the 5 sublayers. Older participants showed a lower percentage of IPL with identifiable sublayers, along with a lower contrast variance within the IPL. Aging also correlated with reduced inner retinal thickness, including the IPL, NFL, and GCC, with a stronger association for the IPL. Inner plexiform layer analysis exhibited high intraeye and intereye repeatability, with significant correlations and nonsignificant mean differences observed in most key parameters. Conclusions: Analysis of the IPL and its sublayers is both feasible and reproducible using commercially available OCT along with a semiautomated segmentation program. Our findings indicate that the IPL microstructure changes with aging. A comprehensive evaluation of the IPL could serve as a valuable biomarker for early diagnosis and monitoring of diseases affecting synaptic health in this layer. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.